Inference of human evolution through cladistic analysis of nuclear DNA restriction polymorphisms. - Mountain, J L (1994)
Testing of nuclear DNA polymorphisms in human populations has been extended to closely related primates. For many polymorphisms, one allele is shared by two or more species: such shared alleles are likely to be ancestral and provide insight not only into the relationships among the primates but also into the evolutionary history of modern humans. Humans from among eight worldwide populations share an allele with chimpanzees for 62 out of 79 polymorphisms examined. Frequencies of these ancestral alleles strengthen the conclusion that the earliest major separation of modern humans was between Africans and non-Africans. The average time since mutation of the ancestral alleles producing the current set of polymorphisms is estimated to be 700,000 years. While differences among ancestral allele frequencies in human populations suggest that natural selection may have played a role in the evolution of a subset of these polymorphisms, simulations indicate that a European bias in the ascertainment of polymorphisms may be at least partially responsible for observed differences. Simulations also suggest that observed heterozygosity levels in African populations, for classical polymorphisms and restriction fragment length polymorphisms, are artificially low due to the same bias. Observed patterns of mean heterozygosity and mean ancestral allele frequency provide support for the hypothesis that Europeans and northeast Asians are closely related. This work suggests that polymorphisms should be selected by testing a random sample of extant humans.